2005
DOI: 10.1158/0008-5472.can-05-0237
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl Isothiocyanate and Sulforaphane and their N-Acetylcysteine Conjugates Inhibit Malignant Progression of Lung Adenomas Induced by Tobacco Carcinogens in A/J Mice

Abstract: We have shown previously that naturally occurring isothiocyanates derived from cruciferous vegetables and their N-acetylcysteine conjugates inhibit lung adenoma formation induced by tobacco carcinogens in A/J mice at the postinitiation stage. The tumor-inhibitory activity by these compounds is linked with activation of activator protein and induction of apoptosis in lung tissues, suggesting that these compounds may also inhibit the development of adenomas to adenocarcinomas in lung. In this study, the chemopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
172
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(177 citation statements)
references
References 48 publications
(64 reference statements)
5
172
0
Order By: Relevance
“…Phenethyl isothiocyanate anatagonised the carcinogenicity of the tobacco carcinogen NNK and inhibited DNA-adduct formation in rat [9]. Finally, the malignant progression of lung adenomas induced by a mixture of benzo[a]pyrene and NNK was inhibited by sulforaphane (1-isothiocyanato-4-(methylsulphinyl) butane) and phenethyl isothiocyanate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Phenethyl isothiocyanate anatagonised the carcinogenicity of the tobacco carcinogen NNK and inhibited DNA-adduct formation in rat [9]. Finally, the malignant progression of lung adenomas induced by a mixture of benzo[a]pyrene and NNK was inhibited by sulforaphane (1-isothiocyanato-4-(methylsulphinyl) butane) and phenethyl isothiocyanate [10].…”
Section: Introductionmentioning
confidence: 99%
“…The plant product sulforaphane [1-isothiocyanato-4-(methylsulfinyl)butane], derived from glucosinolates present in broccoli and other cruciferous vegetables (3), has served as a prototype for our understanding of chemoprotection by induction of phase 2 cytoprotective enzymes including NAD(P)H:quinone oxidoreductase (NQO1) (4). A broad series of animal and human studies has demonstrated the potential of sulforaphane to protect against the onset, or reduce the severity, of cancer (5)(6)(7)(8), retinal disease (9), and skin damage (10)(11)(12) resulting from oxidative or electrophile damage (5,6,8), UV irradiation (10,11), or genetic predisposition (9,13).…”
mentioning
confidence: 99%
“…One potential use of Brassica wastes based on the antimicrobial properties of glucosinolates and their isothiocyanate breakdown products has been as a biofumigation agent for control of soil borne pathogens as an alternative to methyl bromide soil fumigation. Approaches using both dried and fresh material, and in the use of Brassica species as green manures have been investigated in a number of studies (reviewed in [32]). A commercial green manure BQ Mulch TM consisting of a mixture of Brassica species has been developed and marketed in New Zealand for control of soil nematodes and soil pathogens such as Phytophthora and Pythium [98,166] and there are approaches to develop Brassica derived biocidal dried plant pellets for biofumigation [88].…”
Section: Novel Uses For Crop Wastesmentioning
confidence: 99%